Evaluating the water quality within the reticulation system of Kwekwe municipality during the dry and wet seasons - Chinomona, Silence (Midlands State University, 2017)
The research sought to evaluate the water quality within the reticulation system of Kwekwe municipality during the dry and wet seasons and to measure the water quality parameters such as pH, turbidity, total coliforms, free and combined chlorine from the source, final stage of treatment and throughout the distribution system. It also had to consider how distance from one sampling point to another affect the quality of water. It had to consider measurement, the water treatment process, causes for poor water quality as well as desired international standards of World and Health Organisation, (WHO). Data was collected from nine different sampling points including schools, clinics, residential areas of Mbizo and Amaveni, Dutchman Pool Waterworks formerly known as Sebakwe Treatment Works as well as dam water. The data was collected in January and February 2016 representing wet season as well as in May and June 2016 representing dry season. Laboratory tests were conducted in order to analyse the quality of water at the different sampling sites. For statistical analysis both one way and two way ANOVA were used. Regression analysis was done to establish a relationship between water quality parameters and distance.